GAYA KEPEMIMPINAN TERHADAP MOTIVASI BERPRESTASI GURU SMAIT AL-'ARABI CIKARANG BARAT - Ari Yanto; Mansur; Dewi Yanti (UNISAN JURNAL, 2024)
This research aims to explain the influence of the principal's leadership style and achievement motivation on teacher performance at SMAIT AL-'ARABI West Cikarang. The population of this study includes all teachers at SMAIT AL-'ARABI West Cikarang, totaling 31 people. The sampling methods used in this research were personal interviews and internet interviews. Data analysis uses multiple linear regression analysis. The results of research using a partial Multiple Linear Regression test show that the principal's leadership style has a significant effect on teacher performance and achievement motivation has a significant effect on teacher performance, while simultaneously (simultaneously) leadership style and achievement motivation have a significant effect on teacher performance.